Description of Science Literacy Epistemic Knowledge Ability of Chemistry Education Students on the Material of Colligative Properties of Solutions - Ulwan, Rahmad; Enawaty, Eny; Muharini, Rini; Hairida, Hairida; Lestari, Ira (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The ability of science literacy epistemic knowledge is a fundamental thing that must be owned by students in facing the global era to be able to meet the needs of life in various situations. Epistemic knowledge can be said to be a more advanced level of knowledge because epistemic knowledge is closely related to the process of knowledge construction. This study aims to determine the science literacy skills of chemistry education students on the material of colligative properties of solutions. The research method used was a descriptive quantitative method. The study used a sample of 25 samples of 6th semester and 4th semester students using purposive samples. Data collection techniques in this study through measurement techniques and direct communication techniques. The research instrument used in this research is a science literacy test that has been modified and adapted to the material of the colligative properties of the solution. The validation used in this study used construct validity and was validated by judgment experts in material and literacy with valid final results. The results of the research on the ability of epistemic knowledge of science literacy of chemistry education students FKIP Untan shown based on the test of science literacy skills with epistemic knowledge of science literacy on indicators explaining the process of scientific phenomena with an average percentage of 75% with sufficient category. Explaining observations of scientific phenomena with an average percentage of 74% with a sufficient category. Concluding scientific phenomena with an average percentage of 69% with a sufficient category. The overall total average of students' science literacy skills is 73.33% with a sufficient category.